2016
DOI: 10.4238/gmr.15036840
|View full text |Cite
|
Sign up to set email alerts
|

HPV genotyping and p16 expression in Xingu Indigenous Park, Brazil

Abstract: ABSTRACT. The association between high-risk human papillomavirus (HPV) genotypes and p16 expression in indigenous women from the Xingu Indigenous Park, Brazil, was unknown. This study evaluated p16 expression in women with a histological diagnosis of cervical intraepithelial neoplasia (CIN) 3 or higher and correlated this expression with HPV genotypes to determine possible discrepancies in the expression of this marker. We evaluated 37 previously collected samples with different HPV genotypes and high-grade le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In Xingu, it was reported the prevalence of HPV 52 and HPV types of possible high oncogenic risk in high grade lesions, inferring the possibility of a different epidemiological profile than expected. Consequently, the efficacy of immunization through the quadrivalent or nonvalent vaccine in this population should be considered judiciously [2]. In conclusion, the paradigm that organization is indeed the best step to implement cancer prevention was demonstrated.…”
Section: Igrwh000559 3(2)2019mentioning
confidence: 95%
See 1 more Smart Citation
“…In Xingu, it was reported the prevalence of HPV 52 and HPV types of possible high oncogenic risk in high grade lesions, inferring the possibility of a different epidemiological profile than expected. Consequently, the efficacy of immunization through the quadrivalent or nonvalent vaccine in this population should be considered judiciously [2]. In conclusion, the paradigm that organization is indeed the best step to implement cancer prevention was demonstrated.…”
Section: Igrwh000559 3(2)2019mentioning
confidence: 95%
“…among others [1,2]. In addition, available epidemiological data are insufficient to assess the health problems of the female population and of indigenous adolescents [3].…”
Section: Igrwh0005559 3(2)2019mentioning
confidence: 99%
“…Regarding the analysis of CT detection, it was observed that 1.8% (18) of women were positive. The distribution analysis by XIP region showed that 38.9% (7) were from Lower Xingu, 27.8% (5)…”
Section: Ethics Approvalmentioning
confidence: 99%